HVDC Transmission Simulation and Modeling - Zhang, Wenhang; Jin, Jun (International Journal of Mechanical and Electrical Engineering, 2024)
HVDC transmission is a new transmission technology, but it is born with specialties, such as large transmission capacity, skillfully small transmission loss, long transmission distance, and relatively flexible and rapid transmission control. Therefore, HVDC power transmission technology develops rapidly in various countries around the world. Through the principle of HVDC transmission, analyzes the basic principle and hierarchy of HVDC system management, studied the basic components of management system, established the simulation model based on PSCAD / EMTDC model, and tested the principle and performance of HVDC system, DC transmission control trigger switch and transformer adapter. Finally, through simulation, the possible faults in DC transmission operation and the built converter trigger control and cutting filter model are simulated. It can conclude from the simulation waveform diagram that the fault of each device has very different influence on the system. Simulation results verify the correctness and rationality of the design.